Tailoring swelling of alginate-gelatin hydrogel microspheres by crosslinking with calcium chloride combined with transglutaminase. (1st November 2019) - Pilipenko, Nadezhda; Gonçalves, Odinei Hess; Bona, Evandro; Fernandes, Isabel P.; Pinto, João A.; Sorita, Guilherme D.; Leimann, Fernanda Vitória; Barreiro, Maria Filomena
Graphical abstract: Highlights: Alginate-based hydrogel microspheres with variable swelling properties were produced. Alginate ionic crosslinking was combined with Gelatin TGase-induced crosslinking. A systematic study was conducted using CCRD, and PCA statistic tools. Multiobjective optimization validated the developed predictive models. Gelatin content and transglutaminase concentration were the most influential variables. Abstract: Alginate-based hydrogels can find uses in a wide range of applications, including in the encapsulation field. This type of hydrogels is usually ionically crosslinked using calcium sources giving rise to products with limited internal crosslinking. In this work, it is hypothesized that the combination of alginate crosslinked by calcium chloride (external crosslinking; ionic mechanism) with gelatin crosslinked by transglutaminase (internal crosslinking; enzymatic induced mechanism) can be used to tailor the swelling behavior of alginate-based hydrogel microspheres. A systematic study was conducted by covering process variables such as gelatin content, TGase concentration, and CaCl2 contact time, added by statistic tools as central composite rotatable design (CCRD), principal component analysis (PCA) and multiobjective optimization, to map their effect on the resulting water content after production (expressed as swelling ratio), and swelling properties at pH 3 and 7. Among the studied variables, particle's swelling was mostly affected by the gelatin content and transglutaminase concentration.